Regadenoson versus Dipyridamole: A Comparison of the Frequency of Adverse Events in Patients Undergoing Myocardial Perfusion Imaging. Issue 6 (26th May 2017) - Amer, Kallie A.; Hurren, Jeff R.; Edwin, Stephanie B.; Cohen, Gerald
Abstract : Study Objective: To compare the frequency of adverse events in patients undergoing myocardial perfusion imaging (MPI) with either regadenoson or dipyridamole. Design: Single‐center, retrospective cohort study. Setting: Large community teaching hospital. Patients: A total of 568 adults who underwent single‐photon emission tomography MPI with either regadenoson (284 patients) or dipyridamole (284 patients) as a vasodilator agent, following an institution conversion from regadenoson to dipyridamole in the MPI protocol on July 15, 2013, for cost‐saving purposes. Measurements and Main Results: Data were collected from the patients' electronic medical records. The primary endpoint was the composite occurrence of any documented adverse event in each group. Secondary endpoints were individual components of the primary endpoint, reason for termination of the MPI examination (protocol completion or premature end due to an adverse event), use of an interventional agent to an treat adverse event, and cost‐related outcomes. A higher proportion of patients in the regadenoson group experienced an adverse event than those who received dipyridamole (84.9% vs 56.7%, p<0.0001). None of the patients in either group required early MPI study termination due to an adverse event. No significant differences were noted between groups regarding use of aminophylline or other interventions to treat adverse events. The overall drug cost savings in the postconversion dipyridamole group was 51, 526. Conclusion: Dipyridamole was associated with fewer adverse events than regadenoson in patients undergoing MPI. Dipyridamole offers a safe and cost‐effective alternative to regadenoson for cardiac imaging studies.